2018
DOI: 10.1159/000493841
|View full text |Cite
|
Sign up to set email alerts
|

Catalase Enhances Viability of Human Chondrocytes in Culture by Reducing Reactive Oxygen Species and Counteracting Tumor Necrosis Factor-α-Induced Apoptosis

Abstract: Background/Aims: Both physiologic remodeling and pathologic regeneration of cartilage tissue rely upon chondrocyte functions and are benefited from factors that promote viability and inhibit apoptosis of the cell, and associated mechanisms. High level of reactive oxygen species (ROS) and proinflammatory cytokines activate apoptosis signaling and initiate cell death, which can be attenuated by antioxidants. This study examined the effect of catalase (CAT) on ROS and tumor necrosis factor-α (TNF-α)-induced apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Our results demonstrated consistent findings of mitochondrial dysfunction with reduced PGC-1α, decreased mitochondrial DNA copy number and mass in chondrocytes after TNF-α stimulation. In accordance with our findings, one of the previous studies has demonstrated that reduction of oxidative stress in chondrocytes counteracted the upregulated expression of apoptotic cascade factors caused by TNF-α [43], indicating oxidative stress as a key part to the TNF-α-induced apoptosis. The antioxidant deficiency has been revealed in OA chondrocytes with lower SOD activity and an increase of intracellular ROS production [44], and we proved that these changes might occur as a result of TNF-α activation.…”
Section: Discussionsupporting
confidence: 93%
“…Our results demonstrated consistent findings of mitochondrial dysfunction with reduced PGC-1α, decreased mitochondrial DNA copy number and mass in chondrocytes after TNF-α stimulation. In accordance with our findings, one of the previous studies has demonstrated that reduction of oxidative stress in chondrocytes counteracted the upregulated expression of apoptotic cascade factors caused by TNF-α [43], indicating oxidative stress as a key part to the TNF-α-induced apoptosis. The antioxidant deficiency has been revealed in OA chondrocytes with lower SOD activity and an increase of intracellular ROS production [44], and we proved that these changes might occur as a result of TNF-α activation.…”
Section: Discussionsupporting
confidence: 93%
“…Such translational/posttranslational inhibition may also induce the downregulation of catalase following neonatal hyperoxia in the current study. Since catalase enhances cell viability by reducing ROS-induced apoptosis [61], the hyperoxia-induced downregulation of catalase may cause tubular apoptosis, as we observed, and undermine proximal tubular development.…”
Section: Discussionmentioning
confidence: 74%
“…CAT can decompose the hydrogen peroxide into molecular oxygen and water. CAT significantly reduced oxidative stress and restored mitochondrial structure by enhancing the mitochondrial membrane potential ( Δψ m) so as to play an antiapoptotic effect and normalize replicative and wound healing capacity [13, 14]. Glutathione peroxidases (GPxs) consist of multiple isoenzymes with distinct subcellular locations exhibiting different tissue-specific expression patterns [15, 16].…”
Section: Generation Of Ros and Antioxidant Systemmentioning
confidence: 99%